PKM TRAINING ON CREATING DIGITAL BOOK MEDIA BASED ON THE HEYZINE PLATFORM FOR MUHAMMADIYAH ELEMENTARY SCHOOL TEACHERS - Tirtoni, Feri (Antis-publisher, 2025)
Objective: This study aims to enhance the capabilities of elementary school teachers in creating innovative and interactive learning through a digital media training program using the Heyzine platform. Heyzine facilitates the creation of e-magazines and interactive media, addressing the growing demand for technological mastery in education. Method: The training involved demonstrations, hands-on practice, and group discussions to optimize participants' understanding. These methods were structured to accommodate varying levels of technological proficiency among teachers. Results: The training successfully enabled teachers to produce innovative learning materials, including thematic e-magazines, interactive videos, and digital quizzes. These materials significantly improved student engagement in learning. Additionally, participants reported increased technological competence and confidence in integrating digital media into their teaching practices. Novelty: This initiative highlights the practical application of Heyzine as a digital tool for education, bridging the gap between traditional teaching methods and modern technological demands. The study also identifies challenges, such as varying technology skills and limited access to devices, proposing sustainable solutions like follow-up training and continuous mentoring. The findings contribute to the discourse on achieving quality education aligned with national educational goals in the digital age.